Tidal Benchmarking Project Dataset: R001 - Harvey, S; Chen, X; Bhavsar, K; Allsop, T; Benson, I; Mullings, H; Stallard, T; Young, A; Gilbert, J; Vogel, C; Willden, R (University of Oxford, 2022)
The tidal turbine benchmarking project has conducted a large laboratory scale experiment on a highly instrumented 1.6 diameter tidal rotor, with the aim of providing a well-documented experimental dataset that will be used in a benchmarking exercise that will compare a range of modelling methodologies for tidal turbines. This initial dataset, identified as R001, contains the turbine and blade geometry, the benchmarking test cases and 2D CFD data for the blade hydrofoil profile.